Pengaruh Temperatur dan Jenis Reduktor Terhadap Persen Metalisasi dan Persen Fe Hasil Reduksi Bijih Besi Kalimantan - Soesaptri Oediyani; Murti Handayani; Anistasia Milandia (Badan Kerja Sama Pendidikan Metalurgi dan Material (BKPMM), 2018)
One of the natural resources that can be used as an alternative source of reductor is charcoal made from wood and coconut shell. In addition, plastic / polyethylene (PE) can also be used as an additional reducing agent, since PE has hydrogen and carbon chains that can decompose at high temperatures into hydrogen and carbon monoxide gases. Furthermore, in iron making process, temperature also plays an important role. Based on Chaudron diagram, iron ore will be reduced to sponge iron at temperatures above 750°C. Therefore, in this research, the variations of temperature were 800, 900 and 1000°C with 2 hours of reduction time. The raw material consists of briquettes made from a mixture of iron ore and reducing agents. The result of the research shows that the highest metallization is about 97,08% obtained at 1000°C by using coconut shell charcoal and additional of 7.4% PE. In this condition, Fe content in sponge iron is about 62.90%.